One Path, Four Travellers: A PhD Journey of the Mind, Heart, Body and Spirit - Tucker, Allison Lynette; Poff, Jessica; Manitowabi, Melanie; Bruce, Angie (Journal of the Canadian Association for Curriculum Studies, 2020)
As PhD students in Education Sustainability at Nipissing University, the authors each experienced a personal process of becoming and knowing (Absolon, 2011; Miller, 2019). This paper draws on journal entries, personal narratives, various significant artifacts and uses an autoethnographic (Bochner & Ellis, 2016; Holman et al., 2013) process. The paper offers a counternarrative to the solely academic PhD experiences. We consider how holistic learning engages the whole person and is deep, rich and sustaining (Archibald, 2008; Miller, 2000; Sterling, 2001). Through an exploration of how one path was shared by four travelers and personally understood, it is also an opportunity to reimagine learning (Sterling, 2001) as relational and personally meaningful journeys of mind, heart, body and spirit (Wilson, 2008). It focuses on relational learning (Battiste, 2013), communities of trust (Palmer, 1998), inter-sectionality, acknowledgement and acceptance of many ways of being. In this paper, four graduate students share humanized, educational experiences rooted in Indigenous ways of knowing and relationality that are personally constructed and transformative in nature. Their experiences bring about new ways of understanding themselves and extend it to an emergent and deepening understanding of their world views and of who they are as researchers, writers and learners. The four interconnected papers explore each student’s learning journey as it was understood in this context, at this time in life and within this community of learners.